The in vitro metabolism of 11β-hydroxyprogesterone and 11-ketoprogesterone to 11-ketodihydrotestosterone in the backdoor pathway. Issue 178 (April 2018) - van Rooyen, Desmaré; Gent, Rachelle; Barnard, Lise; Swart, Amanda C.
Graphical abstract: Highlights: Adrenal CYP11B1 & B2 catalyse the production of 11β-hydroxyprogesterone (11OHP4). 11βHSD2 catalyses the conversion of 11OHP4 to 11-ketoprogesterone (11KP4). 11OHP4 & 11KP4 are metabolised to 11-ketodihydrotestosterone in the backdoor pathway. SRD5A & AKR1C2 reduce 11OHP4 & 11KP4 to their 3α, 5α-reduced C21 steroids. CYP17A1 catalyses the 17α-hydroxylase and the 17, 20-lyase reaction of alfaxalone. Abstract: Increased circulating 11β-hydroxyprogesterone (11OHP4), biosynthesised in the human adrenal, is associated with 21-hydroxylase deficiency in congenital adrenal hyperplasia. 17α-hydroxyprogesterone levels are also increased, with the steroid's metabolism to dihydrotestosterone in the backdoor pathway contributing to hyperandrogenic clinical conditions. In this study we investigated the in vitro biosynthesis and downstream metabolism of 11OHP4. Both cytochrome P450 11β-hydroxylase and aldosterone synthase catalyse the biosynthesis of 11OHP4 from progesterone (P4) which is converted to 11-ketoprogesterone (11KP4) by 11β-hydroxysteroid dehydrogenase type 2, while type 1 readily catalysed the reverse reaction. We showed in HEK-293 cells that these C11-oxy C21 steroids were metabolised by steroidogenic enzymes in the backdoor pathway–5α-reductase (SRD5A) and 3α-hydroxysteroid type 3 (AKR1C2) converted 11OHP4 to 5α-pregnan-11β-ol, 3, 20-dione and 5α-pregnan-3α, 11β-diol-20-one, while 11KP4 was converted to 5α-pregnan-3, 11, 20-trione and 5α-pregnan-3α-ol-11, 20-dione (alfaxalone), respectively. Cytochrome P450 17α-hydroxylase/17, 20-lyase catalysed the hydroxylase and lyase reaction to produce the C11-oxy C19 steroids demonstrated in the conversion of alfaxalone to 11-oxy steroids demonstrated in the conversion of alfaxalone to 11ketoandrosterone. In LNCaP cells, a prostate cancer cell model endogenously expressing the relevant enzymes, 11OHP4 and 11KP4 were metabolised to the potent androgen, 11-ketodihydrotestosterone (11KDHT), thus suggesting the C11-oxy C21 steroids contribute to the pool of validating the in vitro biosynthesis of C11-oxy C19 steroids from C11-oxy C21 steroids. The in vitro reduction of 11KP4 at C3 and C5 by AKR1C2 and SRD5A has confirmed the metabolic route of the urinary metabolite, 3α, 20α-dihydroxy-5β-pregnan-11-one. Although our assays have demonstrated the conversion of 11OHP4 and 11KP4 by steroidogenic enzymes in the backdoor pathway yielding 11KDHT, thus suggesting the C11-oxy C21 steroids contribute to the pool of potent androgens, the in vivo confirmation of this metabolic route remains challenging.